Unveiling new perspectives about the onset of neurological and cognitive deficits in cerebral malaria: exploring cellular and neurochemical mechanisms - de Lima, Renato M. S.; Leão, Luana K. R.; Martins, Luana C.; Passos, Adelaide da C. Fonseca; Batista, Evander de J. Oliveira; Herculano, Anderson M.; Oliveira, Karen R. H. M. (Frontiers in Cellular and Infection Microbiology, 2025)
Cerebral malaria is the most severe and lethal complication caused by Plasmodium falciparum infection, leading to critical neurological impairments and long-term cognitive, behavioral, and neurological sequelae in survivors, particularly affecting children under the age of five. Various hypotheses have been proposed to explain the neurological syndrome associated to cerebral malaria condition, including vascular occlusion and sequestration, cytokine storm or inflammatory response, or a combination of these mechanisms and despite extensive research and a growing range of scientific information, the precise pathophysiological mechanism remains poorly understood. In this sense, this review aims to explore the neurological impairment in cerebral malaria and elucidate novel mechanisms to explain the severity of this disease. Recent evidence implicates glutamate and glutamatergic pathways in the onset of cerebral malaria, alongside the impairments in the metabolic activity of other molecules such as dopamine and kynurenic acid. These neurotransmitters pathways may play a crucial role in the pathogenesis of cerebral malaria, potentially interacting with other molecular players. By enhancing our understanding in the pathophysiology of cerebral malaria, this article seeks to explore new hypotheses regarding the involvement of neurotransmitters and their interactions with other molecular targets, thereby contributing to the overall pathology of cerebral malaria.